2017
DOI: 10.1074/jbc.m117.776153
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic regulation of cell-cycle and differentiation gene programs in neonatal cardiomyocytes by homologous MEF2 transcription factors

Abstract: Cardiomyocytes acquire their primary specialized function (contraction) before exiting the cell cycle. In this regard, proliferation and differentiation must be precisely coordinated for proper cardiac morphogenesis. Here, we have investigated the complex transcriptional mechanisms employed by cardiomyocytes to coordinate antagonistic cell-cycle and differentiation gene programs through the molecular dissection of the core cardiac transcription factor, MEF2. Knockdown of individual MEF2 proteins, MEF2A, -C, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
0
26
1
2
Order By: Relevance
“…However, MEF2C was relatively more expressed in the intestine than in the other tissues, which revealed that MEF2C was involved in energy production in mitochondria, while MEF2A and MEF2D were related to cellular growth and survival. Conversely, MEF2B was barely expressed in skeletal and cardiac muscles in mice and goats (Desjardins and Naya 2017) but was also largely detectable in skeletal muscle and intestine in our study, the conflicts perhaps caused by different species. Similarly, MEF2A expression is undetectable or weak in the mouse, chicken, and zebrafish (Edmondson et al 1994).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, MEF2C was relatively more expressed in the intestine than in the other tissues, which revealed that MEF2C was involved in energy production in mitochondria, while MEF2A and MEF2D were related to cellular growth and survival. Conversely, MEF2B was barely expressed in skeletal and cardiac muscles in mice and goats (Desjardins and Naya 2017) but was also largely detectable in skeletal muscle and intestine in our study, the conflicts perhaps caused by different species. Similarly, MEF2A expression is undetectable or weak in the mouse, chicken, and zebrafish (Edmondson et al 1994).…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, it was reported that MEF2A, –B, and ‐D were expressed ubiquitously after birth, while MEF2C was restricted to skeletal muscle, brain, and spleen (Breitbart et al ; McDermott et al ). Moreover, MEF2A is expressed ubiquitously at the level of messenger RNA (mRNA) in humans (Yu et al ) and also expressed in vascular smooth muscle cells of rats (Suzuki et al ), particularly highly expressed in neonatal rat ventricular myocytes, where mRNA levels of MEF2A were 22‐ to 25‐fold higher than MEF2C and ‐D and 350‐fold higher than MEF2B (Desjardins and Naya ).…”
mentioning
confidence: 99%
“…The developmental switch from proliferation to hypertrophy is the result of large-scale shifts in gene expression and metabolism, where changes in the expression pattern of the myocyte enhancer factor-2 (MEF2) family appears to be a key event [12][13][14][15]. Genetic studies have shown that three MEF2 genes have non-redundant and potentially antagonistic roles.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown that three MEF2 genes have non-redundant and potentially antagonistic roles. For example, MEF2C has been shown to regulate cardiomyocyte proliferation during cardiac looping, MEF2A promotes cardiomyocyte differentiation and mitochondrial biogenesis, and MEF2D modulates postnatal maturation and remodelling [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation